Sarcomatoid Carcinoma: A Rare and unusual histological variant of prostatic carcinoma - Gupta, Amit; Chaddha, Bhavesh; Prakash, Puneet; Pathak, Priya; Wadhwa, Neelam (Asian Journal of Medical Sciences, 2015)
Carcinosarcoma of Prostate also known as Sarcomatoid carcinoma is a rare biphasic malignancy with a malignant epithelial component (carcinomatous) and a malignant mesenchymal component. We report a case of this rare and unusual histological variant of prostatic carcinoma. DOI: http://dx.doi.org/10.3126/ajms.v6i5.12336 Asian Journal of Medical Sciences Vol.6(5) 2015 69-70